Sorbitol and lactitol reduce body fat and toxic ammonia levels in rats - Shahidul Islam, M.; Nishiyama, Ayae; Sakaguchi, Ei (Nutrition Research, 2007)
Sugar alcohols (SAs) are widely used in various food products because of their benefits on health. The present study investigated the effects of 7% sorbitol or 7% lactitol on nutrient metabolism in cecectomized (CTx) and normal rats. After 16 days of feeding with the experimental diets, food intake was not significantly different, but body weight was significantly decreased in the lactitol-fed groups compared with their respective control groups. The concentration and accumulation of fat in the carcass and the concentration of gut ammonia nitrogen were significantly decreased in both groups of rats fed SAs, and these effects were significantly higher ( P < .05) in CTx rats than in normal rats. Blood urea nitrogen concentration was significantly decreased in the SA-fed groups compared with their control group of normal rats. Lactitol, but not sorbitol, significantly decreased the rate of protein accumulation and the concentration of blood urea nitrogen, respectively, in normal and CTx rats. These data suggest that sorbitol and lactitol can reduce body fat as well as fatty liver condition. Moreover, lactitol is more effective in reducing the parameters studied, which are major risk factors associated with chronic hepatic encephalopathy.